Outcomes of a modified capsular tension ring with a single black occluder paddle for eyes with congenital and acquired iris defects: Report 2. Issue 9 (September 2015) - Date, Rishabh C.; Olson, Michael D.; Shah, Manali; Masket, Samuel; Miller, Kevin M.
Abstract : Purpose : To evaluate the safety and efficacy of Morcher 96F iris diaphragm implantation to manage small defects of the human iris. Setting : Jules Stein Eye Institute, UCLA, Los Angeles, California, USA. Design : Prospective nonrandomized interventional case series. Methods : Demographic, preoperative, and postoperative data of patients who had implantation of the modified capsular tension ring (CTR) and followed to 1 year were reviewed. Safety measures included loss of corrected distance visual acuity (CDVA), perioperative complications, adverse events, and secondary surgical interventions. Efficacy measures included CDVA with glare, daytime and nighttime glare symptom scores, and subjective cosmesis scores. Results : Sixteen patients had CTR implantation. There was a statistically significant improvement in the median CDVA of 2.5 Snellen lines ( P < .01), with 4 patients having minor decreases in CDVA for reasons unrelated to the device. There were no intraoperative complications. Three adverse events were reported: 1 ocular hypertension, 1 postoperative retinal detachment, and 1 25‐degree rotation of the CTR. There were 4 secondary surgical interventions. There was a statistically significant improvement in the median CDVA with glare of 8 Snellen lines ( P < .01), but 2 patients had a decrease in CDVA with glare for reasons unrelated to the device. There were statistically significant improvements in the median daytime and nighttime glare symptom scores of 5 points and 4 points, respectively (both P < .01). There was no change in cosmesis for most patients. Conclusion : Iris diaphragm CTR implantation was relatively safe and effective at reducing light and glare sensitivity in eyes with small iris defects. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.